Examining the Relationship Between Science Investigatory Project Learning Experience and Attitudes Toward Science of Grade 11 STEM Students - Jonathan P. Mellona; Miguel R. Santos (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study aimed to determine the relationship between science investigatory project learning experience and attitudes toward science of Grade 11 STEM students at San Isidro National High School during the school year 2025-2026. The study employed descriptive-correlational research design and gathered data from 28 Grade 11 STEM students through survey questionnaires. Descriptive statistics revealed that Grade 11 STEM students exhibited a very good level of learning experience, in terms of learning engagement, conceptual understanding and collaboration, after the implementation of science investigatory project. Similarly, they demonstrated very good attitudes toward science, in terms of confidence, enjoyment and utility. Meanwhile, inferential statistics revealed that there was a highly significant relationship found between science investigatory project learning experience and attitudes toward science among Grade 11 STEM students with moderate to strong positive correlations (r values ranging from 0.451 to 0.756, p<0.05). This affirmed that science investigatory project learning experiences provide a critical pedagogical approach in fostering positive attitudes toward science. Furthermore, this study encourages teachers to integrate project-based learning, such as SIP, in science teaching. Meanwhile, school administrators may conduct professional development focusing on inquiry-based and project-based teaching strategies. In addition, the proposed action plan must be implemented to improve the learning experience and attitudes toward science through SIP, ensuring sustained improvement in both engagement and scientific disposition.